Integration of Madura's Culinary Tourism Potential in Development Practicum Worksheet for Nutrition and Food Tests in Elementary Science Learning - Wijaya, Bagus Rahmad; Rozie, Fachrur (Widyagogik, 2023)
This study aims to develop valid, effective and practical worksheets for testing food content in science learning in elementary schools. This development research uses the 4D development model, namely: Define, Design, Development, and Dessiminate. The results of the validity of the practicum worksheets for testing food content in science learning in elementary schools were obtained from the average results of 2 validators of 95.35% (very valid). The results of the effectiveness of the practicum worksheets for testing food content in science learning in elementary schools were obtained from student response questionnaires of 85.75%, and student learning outcomes tests of 93.75%. The results of the practicality of the food content test practicum worksheets in science learning in elementary schools were obtained from the observation sheets of teacher and student activities of 94.28%. The results of the research and development of worksheets for testing food content in science learning in elementary schools show very valid, very effective, and very practical results so that they can be used as teaching materials in learning science in elementary schools